Shivering Management in Spinal Anesthesia: Evaluating the Role of Ketamine: A Narrative Review - Siavash Sangi; Mehrdad Mesbah Kiaei; Shahnam Sedigh Maroufi; Maryam Aligholizadeh; Parisa Moradimajd; Azam Saei (Archives of Anesthesia and Critical Care)
Background: Shivering is one of the most prevalent known complications due to dysregulation in the thermoregulatory system following regional anesthesia, with an incidence of 65%, leading to unpleasant outcomes and decreased patient satisfaction. Ketamine, a weak analgesic, affects the thermoregulatory center. Methods: The authors conducted a search and selection of articles using reputable scientific databases. The search keywords included Shivering, Ketamine, and Spinal Anesthesia. The selected articles summarized the literature findings related to ketamine and shivering after spinal anesthesia. Results: This narrative review synthesizes findings from multiple studies examining the role of ketamine in managing shivering following spinal anesthesia. Based on the results obtained, 10 areas were examined: Definition of shivering, Epidemiology of postoperative shivering, Pathophysiology of shivering, Risk factors for post-spinal anesthesia shivering, Spinal anesthesia, its benefits, and its impact on shivering, Post-anesthetic shivering (PAS) complications, Risk factors for postoperative shivering, Control and management of post-anesthetic shivering (PAS) dosage, Effective timing and benefits of ketamine administration in postoperative shivering. Conclusions: The effectiveness of ketamine in preventing shivering after spinal anesthesia is evident from the mixed results of studies. Ketamine, regardless of dosage, can be effective in reducing shivering after spinal anesthesia based on the mentioned criteria. Standardized research with precise methods to determine optimal dosages and ensure safety is necessary.